PROFESSIONAL STRATEGIES OF STUDENTS IN MANAGERIAL SPECIALTIES AT THE STATE UNIVERCITY OF MANAGEMENT (Вестник университета)
The article highlights the actual problem of the formation of professional strategies for students of managerial specialties in the process of studying at a university. The results of empirical research of students are given. On the basis of factor analysis, the place and role of professional strategies in the system of personal life strategies are substantiated. The results of empirical research in the field of higher education are given. The typology of professional strategies is presented and the orientation of career orientations of students in managerial specialties is considered. Identified stable links between professional strategies and personal characteristics of respondents.